2022
DOI: 10.1002/pssb.202200342
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hole Transport Layer and Electron Transport Layer Materials in the Efficiency Improvement of Sb2(Se1−xSx)3 Solar Cell

Abstract: Sb2(Se1−x S x )3 compounds have been regarded as an excellent absorber in thin film solar cells processing. At present, the best efficiency reported in these chalcogenides of antimony corresponds to FTO/CdS/Sb2(Se1−x S x )3/Spiro‐OMeTAD/Au structure with 10.5%. Herein, a comparative study on the Sb2(Se1−x S x )3 solar cell performance with different electron transport layers (ETLs) and hole transport layers (HTLs) is carried out. The main photovoltaic parameters such as short‐circuit current density, open‐circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…From the J – V curve, it can be found that the all-inorganic PSC with BCP buffer layer demonstrates encouraging results with the PV parameters as V OC = 0.75 V, J SC = 39.48 mA/cm 2 , FF = 82.26%, and PCE = 24.66%. This estimated PCE is comparable to the record efficiency of Si-based solar cell’s (∼26.7%) and is found to be larger than the proposed chalcogenides-based devices. Further, to cross validate these results, we also simulated the same device using OghmaNano simulation tool, and the device efficiency (24.64%) aligns well with the SCAPS results (see Figure S6). Figure a inset shows that the device’s EQE, exceeding 99% in 400–700 nm wavelength range.…”
Section: Results and Discussionmentioning
confidence: 99%
“…From the J – V curve, it can be found that the all-inorganic PSC with BCP buffer layer demonstrates encouraging results with the PV parameters as V OC = 0.75 V, J SC = 39.48 mA/cm 2 , FF = 82.26%, and PCE = 24.66%. This estimated PCE is comparable to the record efficiency of Si-based solar cell’s (∼26.7%) and is found to be larger than the proposed chalcogenides-based devices. Further, to cross validate these results, we also simulated the same device using OghmaNano simulation tool, and the device efficiency (24.64%) aligns well with the SCAPS results (see Figure S6). Figure a inset shows that the device’s EQE, exceeding 99% in 400–700 nm wavelength range.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In recent years, single-junction lead halide perovskite solar cells (PSCs) have shown rapid improvement in their power conversion efficiency (PCE), exceeding values of 25% . PSCs have become the most discussed photovoltaic technology during these years, attracting huge attention due to their various applications, low cost, and high performance in next-generation photovoltaics. The unique optical, electronic, and physical properties of lead halide perovskites and optimization in device architecture with suitable stoichiometry and choice of appropriate materials for the hole transport layer (HTL) and an electron transport layer (ETL) , are the main aspects for the rapid growth of PSCs. Despite the exceptional growth in the field, more improvement is required to achieve higher PCE and cost-effective commercialization , of the PSC technology.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, selecting an appropriate hole transport layer to replace the Spiro-OMeTAD still attracts a lot of attention in Sb 2 (S,Se) 3 solar cells. Numerous materials have been used for HTLs in Sb 2 (S,Se) 3 solar cells to improve the carrier transport and suppress carrier recombination of the device, such as CsPbBr 3 , 15 MnS, 16 MoO 3 , 17 PbS, 18 NiO, 19 Cu 2 O 19 and DTPThMe–ThTPA. 20 Among various organic and inorganic p-type semiconductors, the low price and simple preparation process of phthalocyanines is more suitable for use compared to Spiro-OMeTAD.…”
Section: Introductionmentioning
confidence: 99%